Pengembangan Sistem Informasi Jual Beli Pisang Pada UKM Kampung Cau Padjadjaran Jawa Barat - Ardiansah, Irfan; Kastaman, Roni; Harnesa Putri, Selly; Pujianto, Totok; Andrianto Trilaksono, Rafli (POLITEKNIK NEGERI JAKARTA, 2022)
Bananas are a popular fruit in Indonesia, where banana plantations can be found from Aceh to Papua, with a total harvest of 105.801 tons in 2019. Kampung Cau Padjadjaran (UKM KCP), with partner farmers in various regions, is one of the SMEs that manage banana farmers in West Java. The issue is that banana purchases and sales between KCP SMEs, consumers, and farmers are still done manually, resulting in a longer transaction process. Based on this, an Android-based application was created to manage KCP SMEs' buy and sell transactions. Customers can use their smartphones to check banana stocks and process transactions by installing this app. The app is built with the Object-Oriented Programming (OOP) method and the Android Studio framework, as well as a Firebase database that uses cloud technology. This application is called MyBanana, and it has several features that assist consumers, farmers, and KCP SMEs in managing data, information, and transactions, such as the Sign-Up and Login process, which provides security for users to make transactions, and the Banana Type List, which informs the type of banana consumed. The availability of banana stocks is updated in real-time by UKM KCP, and the buying and selling transaction process is simple. The black box test results show that the built application has the features expected by KCP SMEs and functions properly.